Osiadanie Półprzestrzeni Konsolidującej pod Działaniem Obciążenia Skupionego w Przypadku Powierzchni Nieprzepuszczalnej dla Cieczy - Sobczyńska, Z. (Engineering Transactions, 1967)
The problem considered in the present paper is that of a consolidating semi-infinite body loaded by a concentrated force acting on the surface. It is assumed that this surface is absolutely impermeable to liquids. The considerations are based on the theory of flow of liquids through porous deformable bodies formulated by Biot. As a result of solution of the equations of the linear consolidation theory an equation is obtained enabling us to determine the relative subsidence of the surface in the course of time. The solution obtained can be used as Green’s function for the obtainment of the solution for any load acting on the boundary. Finally, diagram of relative subsidence of the surface are presented for sandstone at the time t = 1 sec, t = 1 h, and t = 0. The latter diagram coincides with the result known from theory of elasticity under the name of Flamant’s solution for a elastic medium. It is also shown that there is no subsidence at t = 0. This would contradict the suggestion made by Biot and other authors, that there exists immediate subsidence.